METALLOSTATIC PRESSURE FUNCTION IN THE QUALITY OF Al-Si ALLOY CASTINGS MADE IN SAND MOULDS (Metallurgy and Foundry Engineering, 2015)
The paper presents results of the studies regarding influence of metallostatic pressure of AlSi7Mg alloy on surface roughness of castings prepared in sand moulds as well as on alloy’s density. Castings in a cylindrical shape with a diameter of 15.0; 25.0 or 3.5 mm and height of 700 mm that were cast in a vertical orientation are investigated. The melted alloy was poured into moulds in two ways: bottom up, and top down. Higher pressure and larger diameter of castings favors increaseof surface roughness. In the analyzed range of height of a metal column, density increases linearly: for instance, in case of castings with diameter of ø25 mm, the density increases from ρ = 2.60 g/cm3 to ρ = 2.68 g/cm3, what is about 0.10 g/cm3. In the roller with larger diameter, the density is slightly smaller, however the range of changes along the longer axis is similar to that in the cylinder with diameter of ø25 mm. Additional, ultrasonic studies were performed, which prove that with small changes of the alloy density, velocity of a longitudinal wave changes only slightly. Thus, it is difficult to control small variations (Δρ < 0,10 g/cm3) in density of AlSi7Mg alloy with ultrasonic technique.